2019
DOI: 10.1111/cid.12741
|View full text |Cite
|
Sign up to set email alerts
|

Sinus floor elevation using particulate PLGA‐coated biphasic calcium phosphate bone graft substitutes: A prospective histological and radiological study

Abstract: Background Poly (lactic‐co‐glycolic acid) (PLGA) is widely used for the development of delivery systems for drugs and therapeutic biomolecules in tissue engineering applications. Particles of biphasic calcium phosphate can be covered by PLGA to change their manipulating characteristics. Purpose Aim of this study was to investigate the radiological and histomorphometric results of the use of PLGA‐coated biphasic calcium phosphate granules in sinus floor elevation and to analyze the underlying molecular processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 36 publications
(69 reference statements)
1
28
0
Order By: Relevance
“…Similarly, 26.9 ± 5.4% and 29.3 ± 9.1% of remaining biphasic calcium phosphate particles have been observed in similar studies (Ohayon, ; Ohayon et al, ). More recently, Flichy‐Fernández found the persistence of 22.0 ± 17.26% of a similar biphasic calcium phosphate biomaterial (Flichy‐Fernández et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, 26.9 ± 5.4% and 29.3 ± 9.1% of remaining biphasic calcium phosphate particles have been observed in similar studies (Ohayon, ; Ohayon et al, ). More recently, Flichy‐Fernández found the persistence of 22.0 ± 17.26% of a similar biphasic calcium phosphate biomaterial (Flichy‐Fernández et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…In fact, we have detected that MSI1 and RUNX2 follow a similar expression pattern during osteogenic differentiation of MSC derived from the oral cavity (Padial‐Molina et al, 2019). MSI1‐positive fibroblast‐like cells in regenerated areas in humans have been demonstrated in other families of biomaterials, as allografts (Galindo‐Moreno et al, 2018) and synthetic materials (Flichy‐Fernández et al, 2019; Olaechea et al, 2019). In the present study, we have also found a statistically significantly higher number of MSI1‐positive cells per mm 2 in the non‐mineralized component of the grafted areas surrounding both combinations of biomaterials.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, NMP is flushed out upon contact with body fluids after the application of PLGA/β-TCP, suggesting that NMP may have a short-term cytotoxic effect [ 20 ], and would therefore not affect bone regeneration at 12 weeks post-operatively. Furthermore, preclinical and clinical studies comparing PLGA-coated biphasic calcium phosphate granules to the identical uncoated biphasic calcium phosphate granules showed no negative effects of the PLGA coating nor the addition of NMP [ 13 , 14 ]. This result suggests that the coating is unlikely the cause of the delayed bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of β-TCP used in this study, it was better to use the identical β-TCP if the objective of the present study was the analysis of the effect of PLGA and/or NMP on bone regeneration. However, it was already studied in the previous study referred above [ 13 , 14 ]. Then, we thought it was reasonable to evaluate the safety and efficacy of PLGA/β-TCP for alveolar ridge preservation in extraction sockets compared to an already authorized material, because we aimed to get marketing authorization of the PLGA/β-TCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation